Alma Observations of the Hd 110058 Debris Disk - Perez-Marquez, S (Institute of Physics, 2022)
We present Atacama Large Millimeter/submillimeter Array (ALMA) observations of the young, gas-rich debris disk around HD 110058 at 0.″3-0.″6 resolution. The disk is detected in the 0.85 and 1.3 mm continuum, as well as the J = 2-1 and J = 3-2 transitions of 12CO and 13CO. The observations resolve the dust and gas distributions and reveal that this is the smallest debris disk around stars of similar luminosity observed by ALMA. The new ALMA data confirm the disk is very close to edge-on, as shown previously in scattered-light images. We use radiative transfer modeling to constrain the physical properties of dust and gas disks. The dust density peaks at around 31 au and has a smooth outer edge that extends out to ∼70 au. Interestingly, the dust emission is marginally resolved along the minor axis, which indicates that it is vertically thick if truly close to edge-on with an aspect ratio between 0.13 and 0.28. We also find that the CO gas distribution is more compact than the dust (similar to the disk around 49 Ceti), which could be due to a low viscosity and a higher gas release rate at small radii. Using simulations of the gas evolution taking into account the CO photodissociation, shielding, and viscous evolution, we find that HD 110058 s CO gas mass and distribution are consistent with a secondary origin scenario. Finally, we find that the gas densities may be high enough to cause the outward drift of small dust grains in the disk. © 2022. The Author(s). Published by the American Astronomical Society.